The History and Origin of Fraud as a Defect in Consent in Contractual Relationships - Hajdari, Egzonis (Brawijaya Law Journal, 2021)
Fraud is a specific type of defect in consent that manifests the purpose of one of the parties to establish a contractual relationship through deceptive actions. As such, fraud is an unlawful and unethical action that emerged beginning with some of the earliest agreements in human society. Moreover, the practical treatment of fraud is likely to have occurred since the genesis of its appearance. More appropriate and advanced treatment of fraud can be seen after the implementation of the first legal systems, which focused on contractual relationships. Fraud in contractual relationships will be examined starting with Babylonian, Ancient Greek, Roman, and Islamic law and will continue with a focus on Albanian customary law and modern laws implemented in Kosovo. Furthermore, in this article, we will show how the treatment of fraud has evolved in the legal framework in Kosovo.